From the butterfly’s point of view: Learned colour association determines differential pollination of two co-occurring mock verbains by Agraulis vanillae (Nymphalidae) - Drewniak, María Eugenia (2020)
Learning plays an important role in the location and utilization of nectar sources for pollinators. In this work we focus on the plant-pollinator interaction between the butterfly Agraulis vanillae (Nymphalidae) and two Glandularia plant species (Verbenaceae) that grow in sympatry. Bioassays using arrays of artificial flowers (red vs. lilac-purple) showed that naïve A. vanillae butterflies do not have innate colour preferences for any of the tested colours. Trained butterflies were able to learn to associate both floral colours with the presence of nectar rewards. Wild A. vanillae butterflies visited the red flowers of Glandularia peruviana much more frequently than the lilac-purple flowers of Glandularia venturii. Standing nectar crop measurements showed that G. peruviana flowers offered three times more sucrose than the flowers of G. venturii. Analyses confirmed that corolla colour of G. peruviana (red flowers)and G. venturii (lilac-purple flowers) were discriminable in the butterfly?s colour space. These findings may indicate flexibility in A. vanillae preferences due to a learned association between red coloration and higher nectar rewards.